Andrographolide Attenuates Gut-Brain-Axis Associated Pathology in Gulf War Illness by Modulating Bacteriome-Virome Associated Inflammation and Microglia-Neuron Proinflammatory Crosstalk - Punnag Saha (Brain Sciences, 2021)
Gulf War Illness (GWI) is a chronic multi-symptomatic illness that is associated with fatigue, pain, cognitive deficits, and gastrointestinal disturbances and presents a significant challenge to treat in clinics. Our previous studies show a role of an altered Gut–Brain axis pathology in disease development and symptom persistence in GWI. The present study utilizes a mouse model of GWI to study the role of a labdane diterpenoid andrographolide (AG) to attenuate the Gut–Brain axis-linked pathology. Results showed that AG treatment in mice (100 mg/kg) via oral gavage restored bacteriome alterations, significantly increased probiotic bacteria Akkermansia, Lachnospiraceae, and Bifidobacterium, the genera that are known to aid in preserving gut and immune health. AG also corrected an altered virome with significant decreases in virome families Siphoviridae and Myoviridae known to be associated with gastrointestinal pathology. AG treatment significantly restored tight junction proteins that correlated well with decreased intestinal proinflammatory mediators IL-1β and IL-6 release. AG treatment could restore Claudin-5 levels, crucial for maintaining the BBB integrity. Notably, AG could decrease microglial activation and increase neurotrophic factor BDNF, the key to neurogenesis. Mechanistically, microglial conditioned medium generated from IL-6 stimulation with or without AG in a concentration similar to circulating levels found in the GWI mouse model and co-incubated with neuronal cells in vitro, decreased Tau phosphorylation and neuronal apoptosis. In conclusion, we show that AG treatment mitigated the Gut–Brain-Axis associated pathology in GWI and may be considered as a potential therapeutic avenue for the much-needed bench to bedside strategies in GWI.